REVIEWING GLOCALIZATION OF LIBRARY SERVICES ON THE DIGITAL BUDAYA INDONESIA LIBRARY WEBSITE - Za’imatunnisa’ Za’imatunnisa’; Mega Alif Marintan (2024)
This article aims to determine efforts to glocalize library services on the Perpustakaan Digital Budaya Indonesia website. The website is a forum for accessing, maintaining and preserving online cultural riches in Indonesia. In the current digital era, libraries must pay more attention to glocalization services through websites because they are easy to access and have many features. Glocalization here refers to combining global and local aspects, where the service meets users local needs but still follows international trends. The research method used is qualitative, which is conducted through content analysis. This writing identifies the glocalization strategies used by the library to increase the accessibility and relevance of its services. The results of the research are that we can find out the glocalization of library services on the Perpustakaan Digital Budaya Indonesia website, making it easier for users to find out about local history and culture in Indonesia so that the library can maintain a balance between globalization and locality in providing services that are appropriate and competitive in this era. The digital era can continue to develop. The content provided on the Perpustakaan Digital Budaya Indonesia website is diverse and rich in Indonesian culture. Implementing glocalization of library services on websites can make it easier for users to find out about cultural diversity by accessing them efficiently and flexibly.